CHECKING THE THREE-PHASE ASYNCHRONOUS MOTOR CONNECTED TO THE NETWORK IN THE STAR AND DELTA METHOD (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the procedures and mathematical principles for checking three-phase asynchronous motors connected to a network using the star (Y) and delta (Δ) configurations. Understanding the distinction between these two configurations is critical for the efficient and safe operation of such motors. In the star configuration, the motor windings are connected such that one end of each winding converges at a common neutral point, resulting in a higher phase voltage but reduced starting current. Conversely, the delta configuration connects the windings in a loop, with each junction point connected to the power supply, yielding lower phase voltage but higher running current. Additionally, practical steps for visually inspecting, performing continuity tests, and conducting insulation resistance tests are outlined. These checks are essential for verifying proper connections and ensuring the motor's optimal performance. The article concludes by emphasizing the importance of regular maintenance and proper switching between configurations, particularly for motors equipped with star-delta starters. This comprehensive guide serves as a valuable resource for engineers and technicians involved in the installation, maintenance, and troubleshooting of three-phase asynchronous motors, enhancing their understanding and application of these essential industrial components